THE BODY OF GODS (Journal of Teleological Science, 2021)
For Plato, the gods have a body, according to what is found in traditional mythology. However, this does not make him a defender of tradition, as we can see in book II of the Republic , where he condemns poets who represent the gods by attributing to them the appearance and behavior of men. How then can we reconcile these two statements?